AWARENESS ABOUT TOBACCO USE AMONG MEDICAL STUDENTS OF UTTARAKHAND - Sharma, Mohit; Aggarwal, Pradeep; Kandpal, S D (Indian Journal of Community Health, 2011)
Background: Worldwide tobacco is the second most common cause of death. It is the biggest enemy of public health, still people smoke knowing well the consequences. In addition to the high public health costs of treating tobacco-caused diseases, tobacco kills people at the height of their productivity, depriving families of bread winners and nations of a healthy workforce. Tobacco addiction mostly starts at adolescence. Various reasons cited by adolescents being; peer pressure, stress or for fun. Research Question: What is the level of awareness regarding tobacco use among medical students? Objectives: To assess awareness about tobacco abuse among medical students of Uttarakhand. Study Design: Cross-Sectional epidemiological study. Settings and Participants: Medical and Dental students of all professionals excluding Interns of two Medical and two Dental colleges of Uttarakhand were selected for survey. Study Period: May 2008 to October 2008 Sample Size: 400 Medical and Dental students. Sampling Technique: Simple stratified random sampling. Study Variable: A predesigned, pretested, self-administered questionnaire was used for collecting information on Age, Sex, Socio-demographic profile, Knowledge and awareness regarding Tobacco use, etc. Statistical Analysis: Standard statistical package i.e. SPSS, Microsoft Excel. Results: Life time prevalence of tobacco use was found to be 31.75%, the most common reasons cited by students was peer pressure 33.7%. The level of awareness regarding the harmful effects of tobacco smoking was found to be 91.8%. Majority 68.3% of tobacco users think that media plays an important source for creating awareness about harmful effects of tobacco. 83.25% students are against tobacco advertisements and support ban, 84.75% on tobacco use in public place. 83.75% students surveyed believed that the preventive measures taken up by the Government are not sufficient.